Community-based screening and testing for Coronavirus in Cape Town, South Africa: Short report - Neal David; Robert Mash (AOSIS, 2020)
Corona Virus Infectious Disease 2019 (COVID-19) was first reported in Cape Town in March 2020 and the transmission was soon observed in local communities. Cape Town has many vulnerable communities because of poverty, overcrowding and comorbidities, although it has a relatively small elderly population. Amongst the unique and early responses to the pandemic in South Africa has been the strategy of community screening and testing (CST). This process has been drawn from health department's prior adoption of a community-orientated primary care (COPC) approach, which relies on teams of community health workers working in delineated communities to prevent disease and provide early interventions for those at higher risk. The COPC principles were applied in the CST programme, which involved collaboration between facility and community-based teams, linking public health and primary care approaches, careful mapping of cases in highly vulnerable communities, targeted screening around cases, testing of those that screened positive, health education and linkage to primary care. The overall aim was to slow down transmission through early identification and isolation of diagnosed cases. Key challenges involved the designing of a screening tool with appropriate sensitivity and specificity as well as the logistics of staffing, transport, consumables, data collection and capture, security, ablutions and personal protective equipment. Key opportunities included synergies between CST and evolving commitment to COPC in the health system. Key threats were the deteriorating security situation in the most vulnerable communities because of loss of income, food insecurity and CST distrust as well as increasing turn-around-times for test results.